Sclero-conjunctival ischaemia secondary to intra-arterial chemotherapy for retinoblastoma - Lisa McAnena; Zishan Naeem; Catriona Duncan; Fergus Robertson; Mandeep S. Sagoo; M. Ashwin Reddy (American Journal of Ophthalmology Case Reports, 2020)
Purpose: Intra-arterial chemotherapy (IAC), delivered directly to the globe via the internal carotid artery is now an established treatment for retinoblastoma. We report a case of anterior segment ischaemia following treatment with multiple intra-arterial chemotherapy (IAC) infusions. Observations: A 5 month old female presented with bilateral retinoblastoma and was treated with 12 infusions of IAC. Her right eye was enucleated at diagnosis. After her seventh IAC treatment, she developed ipsilateral sixth and third cranial nerve palsies. After the twelfth IAC, she developed an area of conjunctival and scleral ischaemia between 12 and 3 o'clock meridians in her left eye. However, she maintained visual acuity of LogMAR 0.34. Conclusions and Importance: The median number of IAC treatments in large studies is three. It is possible that repeated doses of IAC have an accumulative negative effect on the ocular blood supply, risking anterior segment and neurologic sequelae. This case highlights the significant challenge of balancing the salvage of eyes and vision with the potentially significant morbidity associated with IAC.